Asset‐Level Transparency and the (E)valuation of Asset‐Backed Securities - NEILSON, JED J.; RYAN, STEPHEN G.; WANG, K. PHILIP; XIE, BIQIN (Journal of Accounting Research, 2022)
ABSTRACT As of November 2016, SEC Regulation (“Reg”) AB II requires issuers of certain types of asset‐backed securities (“ABS”) to disclose the credit‐risk attributes of each asset in the underlying pool, a substantial expansion of prior disclosure requirements. We examine how ABS issuers’ asset‐level disclosures under Reg AB II affect the (e)valuation of ABS by investors and credit rating agencies. Using difference‐in‐differences models that compare affected and unaffected types of ABS, we find that these disclosures improve the ability of initial ABS yields and credit ratings to predict the performance of the underlying assets. These results are concentrated in deals with above‐median risk layering in the underlying assets and complexity in the tranching of credit risk. We further find that asset‐level disclosures are associated with lower yields. Lastly, we provide evidence that most prospective ABS investors download asset‐level information during the price formation period prior to ABS issuance.